Analisis Dampak Meditasi Terhadap Kemampuan Mengelola Emosi Diri Siswa Kelas V SD Negeri 1 Bubusan - Ayunah Ayunah; M. Taheri Akhbar; Mega Prasrihamni (Departement of Mathematics Education, 2023)
students' emotional abilities and have a positive impact on emotional management. The purpose of this study was to determine the effect of meditation on the ability to manage students' self-emotions at SD Negeri 1 Bubusan, especially for class V so that they can train their minds to focus or practice calm so they can divert attention. negative energy to positive activity. This type of research uses descriptive qualitative methods using data collection techniques in this study, namely observation, interviews, and documentation. Qualitative descriptive method is a method with data collected in the form of words or sentences as well as pictures that have concrete meaning and understanding. Based on the results of the research conducted, it was shown that meditation which was carried out at SD Negeri 1 Bubusan class V, which consisted of 24 students and 5 students as samples, had a good impact on managing students' self-emotions by applying meditation to children. can have a positive impact on students' abilities. students in managing their own emotions, children are able to manage emotions in class and can train concentration and the mind becomes calmer then can improve moral behavior and mental health to be better than before.